A Kárpát-medencei államtér problémái Trianon után - Csüllög, Gábor (Közép-Európai Közlemények, 2010)
After the Trianon Peace Treaty had come into force, Hungary and its succession states in the Carpathian basin were facing serious problems of spatial structure. The hasty and rough changes in the borders produced different spatial structures on both sides of the borders. The centers of the succession states were outside the basin. The ancient transit routes running across the region were blocked. The borders ceased to function as connectives and they became inactive. Politics following 1920 forced closure and isolation on the majority of the succession states, as a result of which most regions within the Carpathian basin found themselves in a peripheral situation. In Hungary, the external dictate created a situation which reached the country unprepared. The transformation of the internal spatial processes appeared as a strong need from the very beginning, which, as was opposed by the official revisionist politics, took a long time to start.